PRE-SERVICE TEACHERS PERFORMANCE IN IMPLEMENTING TEACHING METHODS AT TEFL CLASS - Maulina, Maulina; Rusli, Tri Indah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2019)
This study aimed to describe the implementation of microteaching activity by pre-service teachers in TEFL 2 class as well as to get an overview of the problems faced during microteaching so that they are able to improve the competence of teaching English later in both schools and other educational institutions. In this study, the method used was descriptive qualitative. The subject of the study were taken purposively by considering the achievement gained in previous subject namely in TEFL I class they reached the average value of 90 out of 100 with the number of subjects four (4) pre-service teachers. Data were collected through observation using video recording and field note as well as semi structured-interview. Aspects to be analyzed were methods used from opening, main, and closing activities by considering the characteristics of the method applied. The results of this study showed that Grammar Translation Method (GTM) and Audio-Lingual Method (ALM) became a method preference during the microteaching. Pre-service teachers showed no hesitation and well prepared in applying the methods. Translation activities, dialogue memorization, repetition technique, word pair technique, and game grammar technique were occurred. Problems faced were the gap between the theories and the practice of teaching methods such as lack of skills in facial and body expression, classroom management, and stresses with noises from classmates as the students